Status of bone strength and factors associated with vertebral fracture in postmenopausal women with type 2 diabetes. Issue 2 (February 2019) - Chen, Fang-Ping; Kuo, Sheng-Fong; Lin, Yu-Ching; Fan, Chih-Ming; Chen, Jung-Fu
Abstract: Objective: The aim of this study was to assess the status of bone mass, microarchitecture, and factors associated with vertebral fracture in postmenopausal women with type 2 diabetes mellitus (T2DM). Methods: We consecutively enrolled 285 women (aged 60.7 ± 6.9 y) with T2DM who underwent bone mineral density (BMD) and trabecular bone score (TBS) assessment using dual-energy x-ray absorptiometry; T8-S1 lateral spine radiographs; laboratory evaluation; and interviews regarding clinical risk factors based on the fracture risk assessment tool (FRAX). Results: Low bone mass and deteriorated bone microarchitecture were observed in 63.2% and 72.6% of women with T2DM, respectively. TBS was correlated with lumbar spine, femoral neck, and total hip BMD. Significant differences in TBS were observed between the normal BMD, osteopenia, and osteoporosis groups. Age, vertebral fracture, and bone-specific alkaline phosphatase significantly differed among groups with different T scores or those classified by TBS categories. Bone-specific alkaline phosphatase was inversely correlated with BMD and TBS but positively with glycated hemoglobin. BMD showed a weaker correlation with vertebral fracture than TBS, TBS and BMD, FRAX, and TBS-adjusted FRAX. Conclusions: Low bone mass and deteriorated TBS were noted in approximately two-thirds of T2DM women and was also associated with vertebral fracture. In addition to aging, poor glycemic control may play an important role in bone remodeling, which may be associated with changes in bone strength in T2DM women. Bone strength together with clinical risk factors has the strongest association with fracture, and may potentially be useful to identify women with T2DM at risk. Abstract : Supplemental Digital Content is available in the text